2010
DOI: 10.1577/t09-149.1
|View full text |Cite
|
Sign up to set email alerts
|

Summer–Fall Distribution of Stocks of Immature Sockeye Salmon in the Bering Sea as Revealed by Single‐Nucleotide Polymorphisms

Abstract: We report stock composition estimates for immature (ocean-age .1 and .2) sockeye salmon Oncorhynchus nerka distributed across the Bering Sea in late summer and fall. We establish a baseline data set composed of single-nucleotide polymorphism markers that can achieve very high accuracies in identifying sockeye salmon stocks from throughout their range in Asia and North America. We demonstrate the capabilities of this data set to address high-seas salmon issues by analyzing samples collected by researchers from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(123 citation statements)
references
References 59 publications
3
115
0
Order By: Relevance
“…Sockeye Salmon from Puget Sound to southeastern Alaska spend most of their time within the Gulf of Alaska where they overlap with, and presumably compete with many species, including Asian Chum Salmon during the winter. Recent genetic evidence also demonstrates North American Sockeye Salmon extend farther northward and westward into the Bering Sea than thought previously where they overlap with Asian Sockeye and Pink Salmon (Habicht et al 2010). Body size for many Sockeye Salmon populations increased from the 1960s until the late 1970s, followed by decreases (Eggers and Irvine 2007).…”
Section: Irvine and Akenheadmentioning
confidence: 86%
See 1 more Smart Citation
“…Sockeye Salmon from Puget Sound to southeastern Alaska spend most of their time within the Gulf of Alaska where they overlap with, and presumably compete with many species, including Asian Chum Salmon during the winter. Recent genetic evidence also demonstrates North American Sockeye Salmon extend farther northward and westward into the Bering Sea than thought previously where they overlap with Asian Sockeye and Pink Salmon (Habicht et al 2010). Body size for many Sockeye Salmon populations increased from the 1960s until the late 1970s, followed by decreases (Eggers and Irvine 2007).…”
Section: Irvine and Akenheadmentioning
confidence: 86%
“…These estimates may be low; Dronova and Spiridonov (2008) reported that Sockeye Salmon catches in Kamchatka were 1.5-3 times higher than reported. However, Russian salmon fisheries primarily occur close to Russia, and although some Canadian Sockeye Salmon are found in the Bering Sea (Habicht et al 2010;Beacham et al 2011), their numbers in the western North Pacific Ocean are low. We therefore think it is unlikely that declining North American Sockeye Salmon survivals after 1991 are a consequence of these salmon being caught in Russian fisheries and not included in marine harvest estimates.…”
Section: Irvine and Akenheadmentioning
confidence: 99%
“…Salmon may have stock-specific spatial distributions in the ocean (Myers et al 2007, Habicht et al 2010, or use different foraging strategies during the marine phase of their lives that may also produce asynchronous population responses to broad-scale changes in climate. For example, marine biocomplexity among salmon stocks may be expressed as stocks using space or prey resources differently in the ocean.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…A composite phenotype for the two loci was used for both the SAMOVA and BARRIER analyses. The phenotype was generated by combining the two genotypes, ordering them alphabetically, and then assigning a numeric code to the resulting composite phenotype (Habicht et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The data for 45 SNP loci included three mitochondrial and 42 nuclear loci described in Elfstrom et al (2006) and Habicht et al (2010). Chinook salmon data were drawn from Seeb et al (2009); data for 52 SNPs included one mitochondrial and 51 nuclear loci (Smith et al 2005a(Smith et al , b, 2007Narum et al 2008).…”
Section: Methodsmentioning
confidence: 99%